Obtaining dyed decorative enamels for products made of gold, silver and copper - Ryzhova, Olga; Gurzhyi, Olga (Eastern-European Journal of Enterprise Technologies, 2016)
The results of developing of colored jewelry enamels on the base of lead-free glass for decorative, artistic and jewelry articles made of gold, silver and copper are presented. The development of enamel coatings of different colors and shades was conducted on one lead-free glass base, which was dyed with ionic dyes during glass founding. The development of colored enamel coatings on the lead–free glass makes it possible to reduce the cost of jewelry enamel and contributes to the solution of ecological problems, connected with the pollution of the environment with lead compounds. The glass which ensures the smooth enamel coating on copper samples (M1 copper with the thickness of 1 mm) was developed in the system of Na2O–B2O3–SiO2–K2O–BaO–TiO2–ZnO–TiO2. It was established that the introduction of additives TiO2, MoO3 and Fe2O3 increases the enamel coatings luster. Adding TiO2 to 15 mass p. and MoO3 to 3,0 mass p. makes it possible to increase the luminosity of enamels (CDR) up to 35 %). Green, mustard, violet, dark-blue and brown enamels were obtained while adding ionic dyes to the composition of the developed glass. In this case, the luster of the obtained enamels is 57–99 %, which indicates a high fusing degree. The scale of the quality evaluation of different color coating was developed, which makes it possible to classify the defects of enamel layer while applying on gold, silver and copper. The work shows possibility of obtaining the enamel coatings of different colors and shades for artistic and jewelry applying to the base of the glass of one chemical composition with different dyes. The application of such enamels will make it possible to simplify the technology of obtaining the finished articles and lower the probability of defect forming on the enamel coating. The developed enamels can be recommended to the tests under production conditions.